The renewable energy targets of the Maghreb countries: Impact on electricity supply and conventional power markets - Bernhard Brand; Jonas Zingerle (Institute of Energy Economics at the University of Cologne (EWI), 2010)
Morocco, Algeria and Tunisia, the three countries of the North African Maghreb region, are showing increased efforts to integrate renewable electricity into their power markets. Like many other countries, they have pronounced renewable energy targets, defining future shares of 'green' electricity in their national generation mixes. The individual national targets are relatively varied, reflecting the different availability of renewable resources in each country, but also the different political ambitions for renewable electricity in the Maghreb states. Open questions remain regarding the targets' economic impact on the power markets. Our article addresses this issue by applying a linear electricity market optimization model to the North African countries. Assuming a competitive, regional electricity market in the Maghreb, the model minimizes dispatch and investment costs and simulates the impact of the renewable energy targets on the conventional generation system until 2025. Special emphasis is put on investment decisions and overall system costs.
Keywords: L94; Q42; Q47; 330; North Africa; Renewable energy sources; Electricity markets; Förderung regenerativer Energien; Regenerative Energie; Elektrizitätswirtschaft; Maghreb-Staaten